Exclamation Pada Judul Video Youtube Bertema Dakwah: Studi Kasus Kanal Youtube Mufti Menk - Rizqi Yusnitasari; I Dewa Putu Wijana (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2023)
This research is a case study about the use of exclamation in a da’wah themed YouTube video title. The data source is a YouTube channel named Mufti Menk. The video titles that contain exclamation were collected. The exclamations were then analyzed based on the form and the use of syntactic instruments. The result of the study shows that the exclamations were found in two forms, i.e. minor sentence (in a form of phrases), and major sentence (in a form of simple sentences, compound sentences, and complex sentences), with some interjections as the supporting components. In addition, some syntactic instruments with different functions were also implemented in the sentences by using direct speech, active and passive sentences, foregrounding, topicalization, repetition, and syntactic compaction through deletion of subject, copula, main clause, ‘it is’, and ‘there is’.